Advancements in the maintenance of skin barrier/skin lipid composition and the involvement of metabolic enzymes. (13th July 2016) - Cui, Le; Jia, Yan; Cheng, Zhi‐Wei; Gao, Ying; Zhang, Gao‐Lei; Li, Jing‐Yi; He, Cong‐Fen
Summary: The human skin barrier has an important role in protection and defense, reflected not only in the ability to resist entry of harmful substances into the human body, but also in the ability to prevent loss of water and nutrients. Once the skin barrier is damaged, the skin may become dry, scaly, and wrinkled, and a series of skin problems may occur. In this article, we review the composition of lipids, such as ceramides, cholesterol, and free fatty acids, in the skin and examine the expression of enzymes related to lipid metabolism, such as kallikreins, elongase of elongation of very long‐chain fatty acids, hydrolases, and lipid synthases. Additionally, we discuss the involvement of these proteins in skin barrier function and structure. The information presented in this review is expected to provide a theoretical basis for the development of skin care products facilitating the maintenance and repair of skin barrier function.